I skjæringspunktet mellom arkeologi og historie - Jarle Erlend Sethre (Heimen)
Abstract This study is based on research on living conditions on a croft in Gjerpen in Telemark. This croft had settlement in the 17th and 18th centuries. Many of the consumer and utility items found on the site are imported goods that must have been acquired through trade and contact with urban locations, both in the area and from the outside world. Production and transport of coal, as well as work for payment at the breeding farm Ødesanni, appear to be possible sources of income. The large quantity of purchased items, and the quality of any of these, make it natural to ask if people on the croft may have had some kind of additional business beyond farm work. The historical sources provide a rather thin and fragmentary image, but testify to far more modest living conditions than the findings indicate.